College Students' Therapy Preferences: The Role of Psychological Mindedness. Issue 3 (2nd July 2016) - Price, Jennifer L.
ABSTRACT: The current study examined expectations and preferences of psychotherapy approach in 225 college students. Psychodynamic-interpersonal (PI) techniques were generally favored over cognitive-behavioral (CB) techniques both in expectations of what is characteristic of a typical therapy session and perceived helpfulness. There was no difference in findings between therapy naïve college students and those with a history of psychotherapy. Psychological mindedness was correlated with PI ratings, but not CB ratings. College counselors may want to emphasize emotional and relational strategies when working with college students and may benefit from examining the psychological mindedness of new clients to assist with determining their treatment plan.